Simultaneous label-free screening of G-quadruplex active ligands from natural medicine via a microfluidic chip electrophoresis-based energy transfer multi-biosensor strategy. Issue 22 (24th August 2017) - Lu, Yi; Yu, Shiyong; Lin, Fengming; Lin, Fankai; Zhao, Xiaocao; Wu, Liqing; Miao, Yunfei; Li, Huanjun; Deng, Yulin; Geng, Lina
Abstract : Chip-electrophoresis-based separation was combined with an RET optical sensor to establish a new sense of a simultaneous label-free multi-drug screening method. Abstract : Rapid screening of active compounds plays a crucial role in the research and application of complex natural medicines. Herein, a new method of simultaneous label-free multi-drug screening based on a selective aptamer-carboxyfluorescein/graphene oxide energy transfer optical sensor combined with microfluidic chip electrophoretic separation is reported. In this study, seven traditional Chinese medicinal monomers were chosen as targets for the screening of G-quadruplex ligands. The screening results of the G-quadruplex active ligands, including daidzein, berberine hydrochloride, jatrorrhizine hydrochloride, and fangchinoline, and non-active ligands, including geniposide and oxymatrine, were consistent with those reported in literature. Moreover, one new potential G4DNA active drug, jujuboside A, was identified. Molecular simulation of the interaction between G4DNA and drugs was also carried out using HyperChem and AutoDock to verify the results of the experimental screening. It further demonstrated the reliability of our strategy. This novel separation and concentration based multi-sensing strategy provides a simple, rapid, and sensitive tool for simultaneous multi-drug screening, which is very meaningful for drug screening and bio-interaction analysis.